Fracture Resistance of Ceramic Laminate Veneers Bonded to Teeth with Class V Composite Fillings after Cyclic Loading - Leyla Sadighpour; Farideh Geramipanah; Vanya Rasaei; Mohammad J. Kharazi Fard (International Journal of Dentistry)
Purpose. Porcelain laminate veneers (PLVs) are sometimes required to be used for teeth with composite fillings. This study examined the fracture strength of PLVs bonded to the teeth restored with different sizes of class V composite fillings. Materials and Methods. Thirty-six maxillary central incisors were divided into three groups (n=12): intact teeth (control) and teeth with class V composite fillings of one-third or two-thirds of the crown height (small or large group, resp.). PLVs were made by using IPS e.max and bonded with a resin cement (RelyX Unicem). Fracture resistance (N) was measured after cyclic loading (1 × 106 cycles, 1.2 Hz). For statistical analyses, one-way ANOVA and Tukey test were used (α=0.05). Results. There was a significant difference between the mean failure loads of the test groups (P=0.004), with the Tukey-HSD test showing lower failure loads in the large-composite group compared to the control (P=0.02) or small group (P=0.05). The control and small-composite groups achieved comparable results (P>0.05). Conclusions. Failure loads of PLVs bonded to intact teeth and to teeth with small class V composite fillings were not significantly different. However, extensive composite fillings could compromise the bonding of PLVs.